Importance Of Geographical Indication for Conservation of Traditional Products - Rajiv D. Kangabam; Medhabati K. and M. Govindaraju (NeBIO, 2013)
Geographical Indication is a name or sign used to protect certain products which are located in geographical specific or origin within the frame work of Intellectual property. The aim of this study is to provide an overview and importance of geographical Indication on the traditional products under the Indian GI and also to provide awareness among the people on the importance of it in social upliftment for rural development. The study highlighted the present status of the GI registration in India and general information for filling a GI.